Combining Sodium Butyrate With Cisplatin Increases the Apoptosis of Gastric Cancer In Vivo and In Vitro via the Mitochondrial Apoptosis Pathway - Li, Yangbo; He, Pengzhan; Liu, Yinghui; Qi, Mingming; Dong, Weiguo (Frontiers in Pharmacology, 2021)
Introduction: The gastrointestinal malignancy, gastric cancer (GC), has a high incidence worldwide. Cisplatin is a traditional chemotherapeutic drug that is generally applied to treat cancer; however, drug tolerance affects its efficacy. Sodium butyrate is an intestinal flora derivative that has general anti-cancer effects in vitro and in vivo via pro-apoptosis effects and can improve prognosis in combination with traditional chemotherapy drugs. The present study aimed to assess the effect of sodium butyrate combined with cisplatin on GC. Methods: A Cell Counting Kit-8 assay was used to assess the viability of GC cells in vitro. Hoechst 33,258 staining and Annexin V-Phycoerythrin/7-Aminoactinomycin D were used to qualitatively and quantitatively detect apoptosis in GC cells. Intracellular reactive oxygen species (ROS) measurement and a mitochondrial membrane potential (MMP) assay kit were used to qualitatively and quantitatively reflect the function of mitochondria in GC cells. Western blotting was used to verify the above experimental results. A nude mouse xenograft tumor model was used to evaluate the anti-tumor efficacity of sodium and cisplatin butyrate in vivo. Results: Cisplatin combined with sodium butyrate increased the apoptosis of GC cells. In the nude mouse xenograft tumor model, sodium butyrate in combination with cisplatin markedly inhibited the growth of the tumor more effectively than either single agent. The combination of sodium butyrate and cisplatin increased the intracellular ROS, decreased the MMP, and suppressed the invasion and migration abilities of GC cells. Western blotting verified that the combination of sodium butyrate and cisplatin remarkably enhanced the levels of mitochondrial apoptosis-related pathway proteins. Conclusion: Sodium butyrate, a histone acetylation inhibitor produced by intestinal flora fermentation, combined with cisplatin enhanced the apoptosis of GC cells through the mitochondrial apoptosis-related pathway, which might be considered as a therapeutic option for GC.